Load-deflection characteristics and force levels of coated nickel titanium orthodontic archwires - Hind D Abaas; Akram F Al-Huwaizi (College of Dentistry/ University of Baghdad, 2015)
Background: Coated archwires have been introduced to improve esthetics during orthodontic treatment. Theaim of the present study was to evaluate and compare the load-deflection characteristics and force levels of six brands of coated nickel titanium orthodontic archwires using palatal and gingival deflection. Materials and methods: Ten round wires (0.016 inch) and ten rectangular wires (0.019x0.025 inch) were obtained from each of six brands (G&H, Opal, Ortho Technology, Dany, Hubit and Astar Companies). The load-deflection properties of these archwires were evaluated by the modified bending test usinga readymade dental arch model in both palatal and gingival directions at 37°C temperature using a universal material testing machine. Forces generated at maximum loading of 2mm and at unloading of 1.5mm were measured. Results: All the wires showed hysteresis and significant differences in their load deflection curves, but these differences were more evident in round wires than in rectangular wires where G&H wires showed the widest loading- unloading deflection curves. The maximum loading force of round wires in gingival deflection were higher than by palatal deflection. The force decline during unloading (plateau gap) ranged between 18 to 34% for round wires and 17 to 37% for rectangular wires. Conclusion: Coated epoxy wires (G&H, Opal, Astar and Ortho Technology) produced lower forces compared to polymer (Dany) and Teflon (Hubit) coated round and rectangular archwire.